Pengaruh Brand Experience Terhadap Brand Trust Melalui Brand Reputation Sebagai Variabel Intervening - Carla Firma Oktipa; Rose Rahmidani (Universitas Negeri Padang, 2023)
The purpose of this study is to determine the influence of brand experience on brand trust through brand reputation as a variable between PT. Lion Mentari Airlines in Padang. This study used causal research. The population of this study was residents of the city of Padang who used Lion Air airline with 97 samples. The data used is primary data obtained by distributing questionnaires. The analysis method used is path analysis with SPSS 15. The results showed that (1) brand experience has a significant and positive effect on brand reputation (2) brand experience has a significant and positive effect on brand trust (3) brand reputation has a significant effect and positive influence on brand trust (4) brand experience has a significant and positive effect on brand trust, if brand reputation as a variable.